Criminal code the making of a cybercriminal. - Wadlow, Thomas (New York ACM, 2006)
Queue's first-ever narrative chronicles one man's transition from small-time hacker to big-time crook.
Keywords: Computing Milieux; Computers and Society; Public Policy Issues; Abuse and crime involving computers; Social issues